ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK PERAWATAN KEHAMILAN USIA DINI DI PANTAI UTARA KABUPATEN KENDAL - Nur Khafidhoh; Bagoes Widjanarko (JURNAL KEBIDANAN, 2018)
In Kendal for 3 years an increasing number of early age pregnant mother and maternal and infant mortality of early age pregnant mother. These deaths are more prevalent in the northern coast than the mountains, while supporting the health infrastructure in the northern coast more complete. The purpose of this study was to determine the factors that influencing the antenatal care practice to early age pregnant mother in the northern coast of Kendal. Type of study is explanatory research using the survey method and cross sectional approach. Subjects were 35 early age pregnantmother third trimester from the coast, was selected for a total sampling. Data were collected through interviews with a structured questionnaire. Tests performed with chi-square bivariate and multivariate logistic regression test. The independent variables are the characteristics (age, reason for marriage, education, and employment), income, knowledge, attitudes, acceptance of pregnancy, family support, spousal support and the support of health professionals. Dependent variables prenatal care practices. The majority of respondents aged 17-19 years old, married on their own, low education, the majority do not work with household income ≥ minimum wage (Rp 843,750.00) as much as 62.9%. Respondents with a much better knowledge of 54.3%, has a good attitude toward prenatal care 57.1%. Respondents who received pregnancy with either 57.1%, of respondents with good family support 57.1%. Support 88.6% a good husband, a good support health workers 57.1%. Respon-dents with good prenatal care 57.1%. There is a relationship between income (p=0.005), knowledge (p=0.016), attitude (p=0.005) and the acceptance of pregnancy (p = 0.034) with the practice of prenatal care. Attitudes, income and the acceptance of the pregnancy together relate to the practice of prenatal care. The dominant factor associated with the practice of prenatal care is the attitude with OR=15.6. Suggested to the Department of Health to develop SOP and antenatal package in high risk pregnant mother spesially to early age pregnant mother. In addition it is necessary jampersal outreach and cooperation between KUA and Health Office for assistance early age brides in choosing contraception.